2020
DOI: 10.1177/1049732320964262
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link Between the Hazards and Value of Work, and Overcoming Risk for Community-Based Health Interventions for Immigrant Latinx Low-Wage Workers

Abstract: Few studies integrate work and immigration as intersecting social determinants of health. We synthesize data from 12 focus groups ( N = 97) originating from two separate community-engaged studies that originally centered on exploring barriers to health and hazards of work among immigrant Latinx women and men to explore the role of work in their overall health and well-being. The three major interrelated themes we drew from this research—hazards of work, value of work, and building agency to overcome risk—provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Similarly, healthcare workers in the study attributed their acceptance to work in rural areas to fear of losing their jobs, lack of jobs and financial needs. Studies looking at why workers remained at post identified directives from management and fear of employees losing their jobs as key factors ( Akintola & Chikoko, 2016 ; Cuervo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, healthcare workers in the study attributed their acceptance to work in rural areas to fear of losing their jobs, lack of jobs and financial needs. Studies looking at why workers remained at post identified directives from management and fear of employees losing their jobs as key factors ( Akintola & Chikoko, 2016 ; Cuervo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These themes were not an explicit focus of Study 1, but rather emerged over the course of analysis and represented a novel and important finding. Given this emergent quality of the themes related to managing paid care, and following existing analyses in which data were blended from studies on related topics [11,20], we sought to build trustworthiness and enrich the depth of our findings [17] by using directed content analysis to explore these themes in a second qualitative study (Study 2) of paid caregiving in dementia (described above) [21]. Specifically, DW reviewed each family caregiver interview transcript from Study 2 and coded text related to the main theme (i.e., family caregiver managing paid care) and the subthemes, with an additional code for emerging subthemes.…”
Section: Discussionmentioning
confidence: 99%
“…Cleaners have indicated that pride in performing their job well is an important dimension of how they value their work. 9 Anecdotal reports by cleaners suggest that they view themselves as playing a key role in creating a "healthy home", a concept that may stem from intertwined hygienic and morally based values about households. Some have extended this view by acknowledging that their own work frees up their clients', particularly women's, time to work or participate in other household tasks and therefore should be valued by society at large.…”
Section: Household Cleanersmentioning
confidence: 99%
“…3 We focus this article on paid reproductive labor particularly, which has historically been devalued due to its association with these forms of unpaid, yet crucial, labor. 4 Specifically, we have studied workers in homeless shelters, 5 school food workers, 6 home care aides, 7,8 and household cleaners, 9 among others. While these groups may seem very different, they share several important characteristics that can help shape our view of the value of paid reproductive labor to society, and the importance of supporting this critical workforce: their work helps to fill critical policy gaps to improve the social determinants of health; they face extreme job precarity; and the interplay between their social and occupational marginalization creates stressors that may harm both their own health and the health of those that their work supports.…”
Section: Introductionmentioning
confidence: 99%